The Impact of Gold Mining on Local Farming Communities in Ghana - Emmanuel Yamoah Tenkorang; Patrick Osei-Kufuor (Journal of Global Initiatives, 2013)
The increase in leases for surface gold mining in Ghana between 1983 and 1998 has had drastic consequences for sustainable land use and management in the country. Most of these leases were for surface mining displacing the original owners from large arable land needed for their livelihoods. This situation makes the local people vulnerable to econom-ic uncertainties. The real benefits accruing to the ordinary Ghanaian in these mining communities is simply taken, for granted as monetary compensation is paid to affected community members. Such palliative payments to people displaced by mining activities do not address the existing vulnerabilities of these mining communities. This study looks at the effects of mining on households, but from the perspective of the needs expressed by individuals living in the mining area. Using descriptive survey research design, a total of 90 respondents were sampled for structured interviews. Furthermore, 27 focus group discussions with different demographic and occupational groups were organized in se-lected communities in the Tarkwa, Obuasi, and Kenyasi mining areas of Ghana. The needs of households identified in this study varied and included access to productive lands, education, and basic necessities of life. However, household needs have not trans-lated into higher levels of development as a result of mining. It is recommended that a proper cost benefits analysis be conducted when the potential for mineral mining is dis-covered in any area before the decision to mine. These analyses should go beyond just the economic indicators to social and development indicators, which include more quality of life issues.